PROSPECT THEORY AND TAX COMPLIANCE: A MICROFOUNDED EQUILIBRIUM PERSPECTIVE - APRILE, Maria Carmela; BUSATO, Francesco; GIULI, Francesco; MARCHETTI, Enrico (Journal of European Economy, 2019)
This paper discusses the capabilities of a class of microfounded equilibrium models, augmented with Prospect Theory elements in the spirit of al- Nowaihi and Dhami (2007), to address several open questions in the analysis of tax evasion and compliance decisions. There are three main results: i) there exists a unique equilibrium with a tax evasion, consistent with the empirical estimates for the United States economy; ii) the model predicts a positive relationship between tax rate and evasion rate, while offering a solution to the so called Yitzhaki puzzle; iii) the «framing effect» plays a significant role in supporting these results; this is a distinctive characterstic of this class of model, typically not present in simple individual choice models. Furthermore, the model also allows us to investigate some potentially relevant effects of labor supply behavior on the tax compliance decisions. JEL: E21; D03; D81; H03.